Coronary artery disease in primary biliary cirrhosis: A systematic review and meta-analysis of observational studies - Patompong Ungprasert (2018)
© 2015 The Japan Society of Hepatology. Aim: To investigate the association between primary biliary cirrhosis (PBC) and risk of coronary artery disease (CAD). Methods: We conducted a systematic review and meta-analysis of published observational studies that reported relative risks, odd ratios, hazard ratios or standardized incidence ratios with 95% confidence intervals (CI) comparing CAD risk in patients with PBC versus non-PBC controls. Pooled risk ratios and 95% confidence intervals were combined using a random-effect model and generic inverse variance of DerSimonian and Laird methods. Result: Four studies with 3362 patients with PBC were identified and included in our data analysis. The pooled risk ratio of CAD in patients with PBC was 1.57 (95% CI, 1.21-2.06). The statistical heterogeneity was low with an I2of 38%. Conclusion: Our study demonstrated a statistically significant increased risk of CAD among patients with PBC.